Winning Hearts and minds in Uruzgan Province - Fishstein, Paul (Tufts Archival Research Center, 2005)
Research in Uruzgan suggests that insecurity is largely the result of the failure of governance, which has exacerbated traditional tribal rivalries. While respondents within the international military did report some short-term benefits of aid projects in facilitating interaction with and collecting information from communities, it appears that corruption, tribal politics, and the heavy-handed behavior of international forces neutralized whatever positive effects aid projects might have delivered.